EKSPERIMENTASI MODEL PEMBELAJARAN PROJECT BASED LEARNING TERHADAP KETERAMPILAN MENULIS TEKS BERITA MAHASISWA PRODI PENDIDIKAN BAHASA INGGRIS - Dewi Juni Artha; Mutia Febriyana; Dian Novianti Sitompul (PIONIR: JURNAL PENDIDIKAN, 2022)
This type of research is pre-experimental research. This research was conducted in three stages, namely pre-test, treatment and post-test. The subjects in this study were 237 students of the UMSU English Study Program. The techniques used to collect the data above include test techniques, observation, and an assessment rubric for writing news texts. The results of the study show that using the Project Based Learning model can improve the learning outcomes of writing news texts for UMSU students. This is evident from the increased student learning outcomes. The research carried out obtained the following results: (1) Student learning outcomes at the pretest stage were in the low category with an average score of 57.36 and at the post test stage they were in the medium category with an average value of 75.92 (3) The results of the analysis shows that there are changes that occur in student attitudes during the learning process in accordance with the results of observations, namely the application of learning using the Project Based Learning model in news text writing skills has an influence on student learning outcomes. Based on this description, it can be concluded that the Project Based Learning increases the skills of writing news texts for students of the UMSU English education study program.